Penerapan Lesson Study For Learning Community (LSLC) pada Mahasiswa Program Studi Pendidikan Biologi FKIP Universitas Tanjungpura - Marlina, Reni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Application of learning community gives many positive impacts such as raising the attitude of caring fellow learners and improving the performance in the group when doing the investigation of a subject matter. Natural Sciences especially biology can not be separated from the investigation activities conducted through demonstration methods and experiments. Implementation of experiments can not be implemented individually, and this is one of the importancecauses of learning community form in the classroom. Through this forum, learners and educators feel helpful and have a shared responsibility to form a learning community that will impact on improving learning quality. This research is conducted by descriptive method with the subject is all students who are active in Biology Education study program. Objects in this study are students who have taken the Basic Teaching Skills Course and Teaching and Learning Strategy. Implementation is done through 3 stages of plan, do, and see (reflection). Learning process data obtained through observation sheet of learning process. While the student response to lesson study implementation obtained from the questionnaire. Descriptive data analysis by changing the score into percentage and categorized or interpreted to be Very Weak, Weak, Medium, Strong, and Very Strong. Based on data analysis, it is found that LSLC implementation process responseget 58% with medium category. Thus it is concluded that the implementation oApplication of learning community gives many positive impacts such as raising the attitude of caring fellow learners and improving the performance in the group when doing the investigation of a subject matter. Natural Sciences especially biology can not be separated from the investigation activities conducted through demonstration methods and experiments. Implementation of experiments can not be implemented individually, and this is one of the importancecauses of learning community form in the classroom. Through this forum, learners and educators feel helpful and have a shared responsibility to form a learning community that will impact on improving learning quality. This research is conducted by descriptive method with the subject is all students who are active in Biology Education study program. Objects in this study are students who have taken the Basic Teaching Skills Course and Teaching and Learning Strategy. Implementation is done through 3 stages of plan, do, and see (reflection). Learning process data obtained through observation sheet of learning process. While the student response to lesson study implementation obtained from the questionnaire. Descriptive data analysis by changing the score into percentage and categorized or interpreted to be Very Weak, Weak, Medium, Strong, and Very Strong. Based on data analysis, it is found that LSLC implementation process responseget 58% with medium category. Thus it is concluded that the implementation o